Analisis Marjin Pemasaran Melinjo di Daerah Istimewa Yogyakarta - Danang Mnaumono (Agro Ekonomi, 1994)
Gnetum is plant which be developed to increase farmer's welfare, but the marketing behaviour is difficult to understand. Based on these reasons, the purpose of the research is to understand and to identify marketing channels, wholesaler role, proportion and establishment pf marketing margin.